Unveiling the PBL impact on communication and teamwork among biology students - Nosi Qadariah; Tuti Kurniati; Natia Afriana Suri; L. Lufri; A. Andromeda; Fatni Mufit (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Communication and collaboration skills are one of the most important competencies for students. This study aims to analyze the development of communication and collaboration skills of students of IAIN Kerinci's Biology Department through the application of the problem-based learning (PBL) model. Using a quantitative descriptive survey approach, this study involved 60 students who had participated in PBL, focusing on 21st Century communication and collaboration skills. Initial observations showed that students' communication and collaboration skills were still low, with an average score below the expected standard. The PBL model is expected to improve these skills by encouraging students to actively discuss, collaborate, and solve problems critically. This research also seeks to explore the influence of PBL in the context of religious-based higher education, as well as effective strategies that can optimize the development of communication and collaboration skills in the department. The results of the analysis showed that the value of student communication skills was 90.8 with a high category, the value of student collaboration skills was 90.1 with a high category during the application of the PBL model.